2010
DOI: 10.1183/09031936.00040710
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with inflammatory cytokine patterns in community-acquired pneumonia

Abstract: Raised systemic levels of interleukin (IL)-6 and IL-10 cytokines have been associated with poorer outcome in community-acquired pneumonia. The aim of our study was to identify potential associated factors with increased levels of IL-6, IL-10, or both cytokines.We performed a prospective study of 685 patients admitted to hospital with communityacquired pneumonia. IL-6 and IL-10 were measured in blood in the first 24 h.30-day mortality increased from 4.8% to 11.4% (p50.003) when both cytokines were higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 38 publications
(29 reference statements)
2
63
0
2
Order By: Relevance
“…Previous treatment with ICS failed to be an independent protective factor against mortality, but it was a protective factor against the development of respiratory complications at admission and during hospitalisation. Thus, we cannot discard the possibility that previous administration of ICS is not only a ''marker of COPD'', but that it may reduce lung inflammatory response resulting in fewer pulmonary complications [22]. In concordance with this hypothesis, different authors have clearly suggested that ICS could diminish CAP severity by modulating the local inflammatory response (lung microenvironment and macrophage activation) [23] and subsequent organ dysfunction [24,25] and, possibly, could even reduce mortality rate [26,27].…”
Section: Discussionmentioning
confidence: 81%
“…Previous treatment with ICS failed to be an independent protective factor against mortality, but it was a protective factor against the development of respiratory complications at admission and during hospitalisation. Thus, we cannot discard the possibility that previous administration of ICS is not only a ''marker of COPD'', but that it may reduce lung inflammatory response resulting in fewer pulmonary complications [22]. In concordance with this hypothesis, different authors have clearly suggested that ICS could diminish CAP severity by modulating the local inflammatory response (lung microenvironment and macrophage activation) [23] and subsequent organ dysfunction [24,25] and, possibly, could even reduce mortality rate [26,27].…”
Section: Discussionmentioning
confidence: 81%
“…Five additional studies are ongoing. Twelve trials suggested a mortality reduction with corticosteroids, most pronounced in patients with severe rather than mild pneumonia, with some imprecision in the results (relative risk (RR) 0.67, 95% CI 0.45-1.01) [2]. The quality of evidence across outcomes was moderate.…”
Section: Rationalementioning
confidence: 91%
“…Lower respiratory infections, the most deadly communicable disease [1], may be characterized by persistent systemic inflammation [2]. Thirteen trials (n = 2005) have investigated varying daily doses (80-400 mg of hydrocortisone-equivalent; i.v.…”
Section: Rationalementioning
confidence: 99%
“…Also, in a 2014 observational study, previous use of ICS in patients hospitalized for CAP was associated with a reduced systemic inflammatory response, as evidenced by lower interleukin (IL)-6 and tumor necrosis factor (TNF)-α levels [Ferrer et al 2014]. Reduction of the pro-inflammatory response in pneumonia could thus lead to less subsequent organ dysfunction and, therefore, better clinical outcomes [Martinez et al 2011]. Against this hypothesis, however, a 2011 observational study on the impact of ICS on pneumonia outcomes in patients with COPD found no significant difference in the levels of markers of systemic inflammation such as C-reactive protein and white cell count [Singanayagam et al 2011].…”
Section: Discussionmentioning
confidence: 99%